Study of resilience in children (4-11 year) of middle and upper-middle class families in Jabalpur, India - Agrawal, Avyact; Singh, Shivraj (International Journal of Contemporary Pediatrics, 2018)
Background: Resilience as “the process of, capacity for, or outcome of successful adaptation despite challenging or threatening circumstances” is one of the more field. Protective factors are “influences that modify, ameliorate, or alter a person’s response to some environmental hazard that predisposes to a maladaptive outcome”. Easy going temperament and good self-regulation have been identified as protective factors in resilience. The ability to self-regulate also seems to be at the core of good interpersonal relationships and peer relationships, rule compliance, reduced risk of depression and anxiety, and a host of other areas fundamental to successful adaptation and functioning. Methods: This study was conducted during period of January 2000 to October 2001. The sample comprised a total number of 400 children between 4-11 years age and their parents and caregivers. The material for the study was drawn from the two private schools situated in Jabalpur city. Tests used in the study were the Chi square test to test statistical significance, test of significance of difference and Correlating the effect of various factors, analysis of variance F statistics was computed. Results: It was found in our study that the older children (8-11 years) were more outgoing, warm hearted, easy going and participating as compared to lower age group (4-7 yrs.) children. Girls were significantly more resilient that boys in both the age groups i.e. 4-7 and 8-11 yrs. The girls were found to be more emotionally stable, calm and face reality in a very cool manner. Academic achievers were found to be more resilient, easy going, accommodating. No any significant differences when children's resilience was compared with their parental educational status. Conclusions: Girls were significantly more resilient that boys. The girls were found to be more emotionally stable, calm and faces reality in a very cool manner. Academic achievers were found to be more resilient, easy going. accommodating and participate in various extracurricular activities. Older children were more outgoing, warm hearted, easy going and participating.